Pelaksanaan Pengangkatan dan Pemindahan Pejabat Administrator Oleh Pejabat Pembina Kepegawaian di Lingkungan Pemerintah Daerah - Azoumy, Nur Ghufran; Haryono, Dodi; Separen, Separen (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2024)
Introduction: Administrator Officials are appointed and determined by the Staff Supervisory Officer. The implementation of the appointment and transfer of administrator officials within the Karimun Regency Government is considered not running optimally. There are administrator officials who sit in office but not in accordance with the requirements specified in PP No.11 of 2017 concerning Civil Servant Management. Purposes of the Research: The purpose of this study is to determine the implementation of the appointment and transfer of Administrator Officials by the Civil Service Supervisory Officials within the Karimun Regency Regional Government, to find out the obstacles and supporting factors in this implementation, and the efforts made by the government against this. Methods of the Research: The type of research conducted is sociological legal research conducted in the Regional Government of Karimun Regency. The data sources used are primary data and secondary data. The data collection techniques used are interviews, observation and literature review. The data is then analyzed which is qualitative in nature and then concluded using a deductive thinking method. Results of the Research: The result of this study is the implementation of the appointment and transfer of Administrator Officials is done through performance appraisal by TPK PNS is not done because it is not found what is called TPK PNS. This causes there are Administrator Officials who are not in accordance with the requirements determined by laws and regulations such as there are officials who are less qualified.